Search and Rescue Organizations and National Medical Rescue Teams (NMRT) - Mücahit Günaydın; Özgür Tatlı; Esra Ersöz Genç (Doğal Afetler ve Çevre Dergisi)
Disaster is a generic name given to an event causing physical, economic and social losses for people and it stops or interrupts the normal life and actions of the people. When looking at the outcomes of disasters, it can be seen that they mostly cause loss of life and property. While some of these losses emerged immediately with the disaster, some may occur after a certain time. Rapid intervention in during and after disaster is extremely important to recovery of people’s life. Many search and rescue organizations were founded in the World in order to intervene to disasters and emergency situations. After the 1999 earthquake that caused a lot of casualties, National Medical Rescue Teams (NMRT), one of the search and rescue organizations of Turkey, was founded in 2004 for the purpose of reducing number of dead and wounded to an acceptable rate by doing accurate and quick intervention for people exposed to disasters. NMRT are teams made up of volunteer health personnel working according to the regulations created by Ministry of Health to provide medical rescue services to victims of disasters and emergencies of all kinds, both domestic and international.